Molecular aspects of abiotic stress resistance in durum wheat - Mastrangelo A.M.; Rascio A.; Mazzucco L.; Russo M.; Di Fonzo N.; Cattivelli L. (Durum wheat improvement in the Mediterranean region: New challenges, 2000)
Physiological parameters, proline accumulation and expression levels of drought related genes were analysed in durum wheat plants at flowering stage, comparing two varieties with different drought tolerance capacity. The imposed drought stress induced a lowering of water potential and of relative water content, a strong increase in proline and expression of drought related genes. The results showed differences in water potential and gene expression, being, the former, more negative and, the latter, higher in the drought tolerant variety Capeity 8 than in the susceptible one Creso. No differences were found in relative water content and in proline accumulation.
Seminar on Durum Wheat Improvement in the Mediterranean Region: New Challenges, 2000/04/12-14, Zaragoza (Spain)